2003
DOI: 10.1182/blood-2002-08-2391
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid enhances arsenic trioxide–mediated apoptosis in arsenic trioxide–resistant HL-60 cells

Abstract: Recent reports indicate a broad spectrum of antileukemic activity for arsenic trioxide (As 2 O 3 ) due to its ability to induce apoptosis via intracellular production of reactive oxygen species (ROS). Despite its potent apoptotic mechanism, As 2 O 3 is not equally effective in all leukemic cells, which has prompted a search for agents enhancing As 2 O 3 efficacy. Recently, evidence has been gathered that the polyunsaturated fatty acid docosahexaenoic acid (DHA) may sensitize tumor cells to ROSinducing anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 46 publications
3
76
0
1
Order By: Relevance
“…In addition, 10 μg/ml JFA contains 3.6 μM oleic acid. Considering that a previous study showed that 25 μM oleic acid did not affect the cell viability of HL-60 cells 15 , we deemed it unlikely that oleic acid in JFA was responsible for the cytotoxic effects on HL-60 cells. As shown in Fig.…”
Section: Figmentioning
confidence: 99%
“…In addition, 10 μg/ml JFA contains 3.6 μM oleic acid. Considering that a previous study showed that 25 μM oleic acid did not affect the cell viability of HL-60 cells 15 , we deemed it unlikely that oleic acid in JFA was responsible for the cytotoxic effects on HL-60 cells. As shown in Fig.…”
Section: Figmentioning
confidence: 99%
“…5,19,20 BSO modulates the cellular glutathione system and can significantly potentiate the effects of As 2 O 3 , converting arsenic-resistant cell lines to a sensitive phenotype. 21,22 Although in vivo effects have been reported for this combination, 23 the observed additive toxicity may not be selective for cancer cells, and BSO itself has not been successfully developed for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52] Studies suggest a broad spectrum of antileukemic activity for As 2 O 3 because of its ability to increase intracellular ROS production. 53 In As 2 O 3 -sensitive cells, such as the APL-derived cell line NB-4, increased intracellular levels of ROSs lead to collapse of the mitochondrial membrane potential, activation of the caspases, and apoptosis. However, cells with intracellular antioxidant defense mechanisms, such as the acute myeloid leukemia (AML)-derived cell line HL-60, are resistant to As 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…HL-60, an acute myeloid leukemia cell line that is resistant to clinically relevant doses of arsenic, shows a 90% reduction in viability along with an increase in apoptosis, an increase in intracellular reactive oxygen species (ROSs) and lipid peroxidation, as well as an up-regulation of Bax when treated with a combination of arsenic and DHA. 30 Further, treatment with oleic acid, a monounsaturated fatty acid that is not susceptible to lipid peroxidation, did not enhance the effect of arsenic treatment. 31 In breast cancer cells, the addition of DHA results in an increase in malondialdehyde, an end product of lipid peroxidation, which increases sensitivity to doxorubicin treatment through oxidative stress.…”
Section: Introductionmentioning
confidence: 99%